Arsenic-Induced Neurotoxicity: A Study on the Brain–Behaviour Circuit - Chayan Munshi; Alpana Mukhuty; Arindam Bandyopadhyay; Paritosh Mondal; Arpan Dey Bhowmik; Pallab Shaw; Shelley Bhattacharya (Proceedings, 2024)
Introduction: Arsenic is a highly toxic metalloid and an environmental contaminant which predominantly affects the aquatic ecosystem [...]